Hydroxylamines as One-Atom Nitrogen Sources for Metal-Catalyzed Cycloadditions - Yu, Jingxun; Luan, Xinjun (Synthesis, 2021)
Transition-metal-catalyzed C–N bond formation is one of the most important pathways to synthesize N-heterocycles. Hydroxylamines can be transformed into a nucleophilic reagent to react with a carbon cation or coordinate with a transition metal; it can also become an electrophilic nitrogen source to react with arenes, alkenes, and alkynes. In this short review, the progress made on transition-metal-catalyzed cycloadditions with hydroxylamines as a nitrogen source is summarized.1 Introduction2 Cycloaddition To Form Aziridine Derivatives2.1 Intramolecular Cycloaddition To Form Aziridine Derivatives2.2 Intermolecular Cycloaddition To Form Aziridine Derivatives3 Cycloaddition To Form Indole Derivatives4 Cycloaddition To Form Other N-Heterocycles4.1 Aza-Heck-Type Amination Reactions4.2 Nitrene Insertion Amination Reactions4.3 Intramolecular Nucleophilic and Electrophilic Amination Reactions5 Conclusion and Outlook
Keywords: N-heterocycles; amination; C–N bond construction; hydroxylamines; transition-metal-catalyzed; C–H functionalization